2022
DOI: 10.1177/01492063211073690
|View full text |Cite
|
Sign up to set email alerts
|

When Not One of the Crowd: The Effects of CEO Ideological Divergence on Lobbying Strategy

Abstract: This paper explores the extent to which CEO ideological divergence influences firm lobbying strategy. Because a CEO’s political ideological disposition is shown to affect firm outcomes, we theorize there are nonmarket strategic implications when the governing party is divergent or convergent from their ideology. Accordingly, we integrate insights from organizational fit literature regarding value congruence and strategic complementarity in order to examine whether CEO political ideological divergence affects l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 101 publications
0
2
0
Order By: Relevance
“…This can be a potential risk for the firm because they also find that intermediaries can shape their client’s agendas. More recently, Nalick et al (2022) finds that when a CEOs ideology diverges from the ideological bents of those in power, internal lobbying decreases more when compared to external lobbying. Future research should continue to further investigate the differences between internal and external lobbyists.…”
Section: The Variety Of Cpa Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be a potential risk for the firm because they also find that intermediaries can shape their client’s agendas. More recently, Nalick et al (2022) finds that when a CEOs ideology diverges from the ideological bents of those in power, internal lobbying decreases more when compared to external lobbying. Future research should continue to further investigate the differences between internal and external lobbyists.…”
Section: The Variety Of Cpa Approachesmentioning
confidence: 99%
“…In a more recent study of investment professionals in the private equity industry, Bermiss and McDonald (2018) found that ideological misfit leads to employee departure and that those who leave join organizations that fit their ideology better. These studies have significant implications because firms are often identified with their CEOs in the public mind and strong political positions by CEOs may have unintended consequences, especially when the CEOs’ political positions are misaligned with their employees (Brown, Manegold, & Marquardt, 2020) or the current political ideologies of those in power (Nalick et al, 2022). The implications of CEO political activism in terms of reactions by financial markets, customer groups, and employees are yet to be researched.…”
Section: Implications For Future Researchmentioning
confidence: 99%